Exploring the Experiences and Challenges of Non-English Teachers in Teaching English at Primary Schools in Poso, Central Sulawesi - Fadhilah Zamzam; Maghfira; Eva Setyarini; Rahayu Prasetya Ningsih; Dewi Rara Amiati; Muhammad Asy’ari (Universitas Islam Ogan Komering Ilir Kayuagung, 2026)
This study aimed to explore the experiences and challenges faced by non-English teachers who were occasionally required to teach English in primary schools when specialized teachers were unable to attend classes. Using a qualitative descriptive approach, data were collected through in-depth semi-structured interviews with three non-English teachers from rural primary schools in Poso Regency, Central Sulawesi. The findings revealed that non-English teachers felt pressured and unprepared due to the lack of prior preparation in English instruction. They experienced difficulties in selecting appropriate teaching methods, pronunciation, and vocabulary, which led to hesitation in acting as language models for students. To cope with these challenges, teachers relied heavily on online resources such as Google Translate and instructional videos. Although these strategies helped maintain classroom activities, instruction often focused on repeating previously taught materials rather than introducing new content, resulting in limited student learning progress and misalignment with curriculum objectives. Despite these constraints, the teachers expressed strong motivation and enthusiasm for professional development. The study highlighted the urgent need for basic English instruction training for non-English teachers to strengthen their linguistic competence and instructional confidence.